Enterprise Architecture Sebagai Strategi Pengembangan Smart Village (Economic Services) Menggunakan TOGAF 9.2 - Gustriandita, Tiara Shalsabilla; Fajrillah, Asti Amalia Nur; Nurtrisha, Widyatasya Agustika (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2023)
Smart Village is a concept that adopts elements from the smart city concept, leveraging information technology. One of the Indonesian government's initiatives is to foster the development of Indonesia by empowering rural areas in pursuit of sustainable development. The selection of target areas is based on the classification of the Developing Village Index, with a focus on villages categorized as "Advanced." Tanjung Lalang Village is an "Advanced" village, making it suitable for implementing the smart village concept to address challenges and harness the village's resources and potential. The research methodology employed in this study is a literature review, which delivers an Enterprise Architecture design solution utilizing the TOGAF 9.2 framework tailored to meet organizational requirements. The findings of this study consist of an EA blueprint and an IT Roadmap for Tanjung Lalang Village, serving as a guide for the smart village development.Keywords: Enterprise Architecture; Smart Village; Economic Services; TOGAF 9.2; Sustainable Development GoalsÂ AbstrakSmart Village adalah suatu konsep yang mengambil komponen dari konsep smart city yang memanfaatkan teknologi informasi. Salah satu program nawacita pemerintah Indonesia adalah meningkatkan pembangunan Indonesia melalui penguatan daerah-daerah perdesaan untuk upaya pembangunan berkelanjutan. Pemilihan obyek penelitian berdasarkan klasifikasi dari Indeks Desa Membangun dengan status desa â€œMajuâ€. Desa Tanjung Lalang merupakan desa berstatus â€œMajuâ€ yang mampu menerapkan konsep smart village untuk membantu menyelesaikan permasalahan dengan memanfaatkan sumber daya dan potensi desa. Penelitian ini menggunakan metode studi pustaka untuk menyediakan solusi perancangan Arsitektur Enterprise dengan menggunakan framework TOGAF 9.2 yang disesuaikan dengan kebutuhan organisasi. Hasil dari penelitian ini berupa blueprint EA dan IT Roadmap di Desa Tanjung Lalang sebagai acuan pengembangan smart village.